Новые данные о флоре Bacillariophyta Беларуси. 1. Сем. Naviculaceae Kutz. - Куликовский, М.С.; Генкал, С.И.; Михеева, Т.М. (Альгология, 2010)
В фитопланктоне р. Свислочь (Респ. Беларусь) обнаружены 113 новых для флоры водотока таксонов, в т.ч. 63 – новых для Беларуси. Выявлены также представители двух новых родов – Nupela Vyverman et Compère и Prestauroneis Bruder et Medlin. Предложено 7 новых таксономических комбинаций. Новые для флоры Беларуси виды характерны для мезотрофных и эвтрофных водоемов с повышенным уровнем pH. In the phytoplankton of the Svisloch River (Belarus Republic) 113 diatom taxa of species and infraspecific rank new for this river have been revealed. Among them 63 taxa are firs t cited for Belarus flora. Genera Nupela Vyverman et Compère et Prestauroneis Bruder et Medlin were not recorded in Belarus before. In the paper 7 new taxonomical combinations are suggested. All revealed taxa are known to prefer mesotrophic and eutrophic alkaline water bodies.